"Take It One Day at a Time and Try to Adjust to What's Going on": Exonerees' Advice to the Newly Exonerated and Future Exonerees About Life Post-Release. (March 2023) - DeShay, Rashaan A.
Wrongful convictions have received increased attention from both scholars and the media over the past several decades. Most of the research on this topic has focused on the factors that contribute to wrongful convictions and policy changes that may help prevent future miscarriages of justice. Scholars have also explored the post-release experiences of those who have been exonerated. Less attention has been paid to the advice exonerees would share with those who have been recently exonerated to help them navigate their new lives. Semi-structured interviews were conducted with individuals who were wrongfully convicted in the southern United States to explore this issue. While acknowledging that the post-exoneration transition could be challenging, the participants noted that they would advise those who are newly exonerated that faith, talking to other exonerees, learning how to be patient with the process, and finding a way to enjoy their new lives were important to navigating this process. This study highlights the value of exploring the perspectives of exonerees to increase our understanding of their experiences, while also using their insight to inform policy that will assist the wrongfully convicted after being exonerated and released from prison.